2013
DOI: 10.1089/ars.2012.5117
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone I Activates the Nrf2-Dependent Antioxidant Response and Protects Against As(III)-Induced Lung Inflammation In Vitro and In Vivo

Abstract: Aims: The NF-E2 p45-related factor 2 (Nrf2) signaling pathway regulates the cellular antioxidant response and activation of Nrf2 has recently been shown to limit tissue damage from exposure to environmental toxicants, including As(III). In an attempt to identify improved molecular agents for systemic protection against environmental insults, we have focused on the identification of novel medicinal plant-derived Nrf2 activators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
88
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 63 publications
6
88
0
Order By: Relevance
“…Nuclear factor erythroid-2-related factor-2 (Nrf2 or NFE2L2) is a critical molecule involved in maintaining a balanced redox potential in the human body and plays an important role in regulating the expression of phase II detoxifying and antioxidative enzymes (29). Nrf2 or NFE2L2 is a basic helix-loop-helix leucine zipper transcription factor that can activate antioxidant genes by binding the antioxidant response element (ARE) in their corresponding promoter areas (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nuclear factor erythroid-2-related factor-2 (Nrf2 or NFE2L2) is a critical molecule involved in maintaining a balanced redox potential in the human body and plays an important role in regulating the expression of phase II detoxifying and antioxidative enzymes (29). Nrf2 or NFE2L2 is a basic helix-loop-helix leucine zipper transcription factor that can activate antioxidant genes by binding the antioxidant response element (ARE) in their corresponding promoter areas (5).…”
Section: Introductionmentioning
confidence: 99%
“…Although both compounds are able to upregulate Nrf2 pathway, the underlying mechanisms may be different. Keap1 was found to be involved in Nrf2 regulation by tanshinone I (29), and epigenetic modulation could also play a major role and potentially be the main mechanism contributing to the upregulation of Nrf2 by TIIA.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Targeting Nrf2 activation with small molecular chemical inducers can enhance the body's antioxidant ability, and has been shown in experimental models to effectively protect the body from tissue damage caused by environmental insults, preventing disease or inhibiting the progression of diseases related to oxidative stress, including diabetes, cancer, cardiovascular diseases, neurodegenerative diseases, chronic obstructive pulmonary disease, pulmonary fibrosis, and inflammation (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Although the Nrf2 program is usually regarded as beneficial, recent work has suggested that high constitutive levels of Nrf2 also bring its "dark" effects (24)(25)(26)(27).…”
mentioning
confidence: 99%
“…Many chemopreventive compounds have been identified as Nrf2 activators so far, and some newly identified Nrf2 activators are becoming potential novel chemopreventive compounds that have been shown in experimental models to effectively prevent disease or inhibit the progression of diseases related to oxidative stress (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). To date, most identified Nrf2 activators are plant-derived chemicals, including sulforaphane (SF), tanshinone I, curcumin, butylated hydroxyanisole, and so on, some of which are in our diet (11,30,31).…”
mentioning
confidence: 99%